Assessment of exploited fish species in the Lake Edward System, East Africa. (5th January 2021) - Musinguzi, Laban; Bassa, Samuel; Natugonza, Vianny; Van Steenberge, Maarten; Okello, William; Snoeks, Jos; Froese, Rainer
Summary: The unknown status of inland fish stocks hinders their sustainable management. Therefore, increasing stock status information is important for sustainable inland fisheries. Fisheries reference points were estimated for five exploited fish species (11 stocks) in the Lake Edward system, East Africa, which is one of the most productive inland water systems. The aim was to ascertain the status of the fisheries and establish reference points for effective management. The reference points were based on four linked stock assessment approaches for data‐limited fisheries. Estimates showed poor stock status with the stocks defined as either collapsed, recruitment impaired or overfished. However, higher catches could be obtained under sustainable management. Estimates of maximum sustainable yield (MSY) and supporting biomass ( B msy ) are provided for 10 of the stocks as targets for rebuilding plans. The immediate target of management should be rebuilding biomass to B msy . Applicable measures include shifting length at first capture to the length that maximizes catch without endangering size structure and biomass, and livelihood diversification out of fisheries.